ANALISIS PELAKSANAAN EKSTRAKURIKULER PRAMUKA TERHADAP KARAKTER DISIPLIN DAN TANGGUNG JAWAB SISWA SDN TLOGOSARI KULON 03 SEMARANG - Sri Oktanto Arif Wijanarko; Asep Ardiyanto (Universitas Ngudi Waluyo, 2020)
This research is based on the importance of applying character education to students. According to the principal who shapes the character of students not only in the home environment, but also in the community and the school environment. The context in this study is; how is the process of implementing Scouting extracurricular at SDN Tlogosari Kulon 03 in forming the character of discipline and responsibility? The purpose of this research is to find out the implementation of Scout extracurricular activities at SDN Tlogosari Kulon 03 Semarang, which is focused on character education and discipline of student responsibilities. This research method is descriptive qualitative research that describes events or phenomena with data in the form of information in the form of descriptions from SDN Tlogosari Kulon 03 Semarang. Data analysis techniques using qualitative descriptive research methods through data collection, data reduction, data presentation, and drawing conclusions which are then concluded in the form of percentages. Based on the results of the analysis of research data from the interviews of two Scoutmaster coaches and the principal, it can be concluded that the Scout extracurricular activities implement the formation of student characters. This can be seen from the results of the study which showed that the discipline of grade 3 students reached 80.13% while grade 4 reached 88.75%. While in terms of class 3 responsibilities reach the category of